Frailty assessment and outcomes in primary care for patients with diabetes during Ramadan: implications for risk evaluation and care plans - Baynouna Alketbi, Latifa Mohammad; Afandi, Bachar; Nagelkerke, Nico; Abdubaqi, Hanan; Al Nuaimi, Ruqaya Abdulla; Al Saedi, Mariam Rashed; Al Blooshi, Fatima Ibrahim; Al Blooshi, Noura Salem; Al Aryani, Aysha Mohammed; Al Marzooqi, Nouf Mohammed; Al Khouri, Amal Abdullah; Al Mansoori, Shamsa Ahmed; et al. (Frontiers in Medicine, 2024)
Frailty is a critical concern for older adults, impacting their susceptibility to adverse events and overall quality of life. This study aims to determine the frailty status of patients 60 years or older in Abu Dhabi Ambulatory Healthcare Services (AHS) and assess its relation to the stress exerted by Ramadan fasting and the occurrence of any adverse outcomes.In this prospective observational study, participants were included if the attending physicians used the IDF-DAR risk stratification assessment tool. A tele-interview was conducted to complete the FRAIL score within six weeks before Ramadan 1444 (CE 2022). The outcome was assessed through another tele-interview and an electronic medical records review after Ramadan.According to the FRAIL assessment tool, of the patients included in the study who were 60 years or older ( 204), half of them, 109 (53.4%), were either frail or pre-frail. Twenty patients were frail (9.8%), that is, one out of ten, and 89(43.6%) were pre-frail. The remaining 95(46.6%) were robust.Using logistic regression to assess the occurrence of adverse outcomes after Ramadan fasting, having a higher frailty score was the third independent risk factor, B=0.4, OR=1.5 (1-2.02-1.86) p value=0.039 for having an adverse event.Identified factors associated with frailty were factors age, increased Albumin Creatinine Ratio, ACR, chronic Kidney diseases (CKD), and ischemic heart diseases Beta=0.27, P value=0.003, Beta=0.24, P value=0.004, Beta=0.2, P value=0.039, Beta=0.18, P value=0.041 respectively. Onethird of frail patients had an event, while the incidence in pre-frail was 11.2%, and among robust patients, 6.3%. Physicians' global assessment of a patient's being frail did not match the structured FRAIL scoring well. Only five (25%) of the twenty patients identified as frail by the FRAIL assessment tool were judged by physicians' global assessment tool as frail or having cognitive function impairment.Frailty is prevalent among elderly patients with diabetes. Disparity exists between subjective and objective frailty assessments, emphasizing the need for standardized evaluation methods. Using the FRAIL tool is recommended for patients aged 60 or older with diabetes in Abu Dhabi.